Pengaruh Manajemen Lingkungan dan Karakteristik Organ Perusahaan terhadap Pengungkapan Emisi Karbon - Nabilah Nur Annisa; Ilham Ramadhan Ersyafdi (Jurnal Akuntansi Publik Nusantara, 2025)
The purpose of this study is to examine the effect of environmental management, characteristics of corporate organs, namely the board of directors and board of commissioners on carbon emission disclosure. The variables studied include ISO 14001 certification, PROPER rating, green investment, board of directors size, board of directors age, gender diversity of commissioners, board of commissioners size, commissioner education level and composition of independent commissioners. The type of study used is quantitative which is secondary and then uses documentation techniques. The population used in this study are companies listed on the LQ45 Low Carbon Leaders index on the Indonesia Stock Exchange, and there are 38 companies that meet the sample criteria from 2022-2023. The results of the study prove that carbon emission disclosure can be influenced by the PROPER rating and green investment variables. While other independent variables are unable to influence carbon emission disclosure.